Improving substrate properties and foxtail millet growth in gold mine tailings using Azotobacter consortium - Hindersah, Reginawanti; Adawiah, Aliya Zahrah; Suryatmana, Pujawati; Sule, Marenda Ishak Sonjaya; Wicaksono, Fiky Yulianto; Dewi, Triyani (Journal of Degraded and Mining Lands Management, 2026)
Improper disposal of mercury (Hg)-contaminated tailings on agricultural fields can reduce land quality for food production. A pot experiment was conducted to evaluate the effect of the Azotobacter consortium, comprising Azotobacter tropicalis S5, A. vinelandii S6a, and A. chrooccocum S9, on the Carbon-to-Nitrogen (C/N) ratio and Hg levels in tailings as well as foxtail millet growth, biomass, and mercury in plants. The experiment used a randomized block design with three levels of Azotobacter liquid inoculant, i.e., 3, 15, and 30 mL per pot, and six replications. The control did not receive inoculant. After six weeks, the treatment did not alter the pH, total nitrogen, organic carbon, carbon-to-nitrogen ratio, or total mercury levels in the soil; however, it did promote an increase in shoot height and leaf number, without affecting plant biomass. Applying 30 mL/pot of Azotobacter inoculant enhanced Azotobacter and total bacterial populations in the rhizosphere. The Azotobacter inoculant did not alter nitrogen uptake but potentially reduced mercury content in the plants. The Pearson’s test showed that Azotobacter levels in the substrate were significantly correlated with the decreased mercury content of plants. These findings suggest that the application of the Azotobacter consortium can lead to improved plant growth and a reduction in mercury uptake by millet plants grown in tailing-based substrate. Further research is necessary to develop more effective inoculants and extend the study period.